2020
DOI: 10.1097/mph.0000000000002033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Children With Relapsed Pancreatoblastoma: A Literature Review

Abstract: Pancreatoblastoma (PB) is a tumor typically seen in childhood. Despite its rarity, there are some internationally agreed recommendations for its first-line treatment, but very little is known about the management of relapse. We reviewed the literature on the treatment and outcome of children with progressing/recurrent PB, and the role of high-dose chemotherapy (HD-CT) or liver transplantation in difficult cases. A first analysis concerned 15 patients: liver metastases were the most frequent cause of first-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The most often used combinations included etoposide, cyclophosphamide/ifosfamide and cisplatin/carboplatin. A review from Reggiani et al [ 37 ] showed that the outcome for patients with recurrent PBL was not always dismal, especially when surgery is possible.…”
Section: Pancreatoblastoma (Pbl)mentioning
confidence: 99%
“…The most often used combinations included etoposide, cyclophosphamide/ifosfamide and cisplatin/carboplatin. A review from Reggiani et al [ 37 ] showed that the outcome for patients with recurrent PBL was not always dismal, especially when surgery is possible.…”
Section: Pancreatoblastoma (Pbl)mentioning
confidence: 99%
“…Nonetheless, PBLs are rare with a recent systematic review identifying 81 pediatric cases since 1980 (5). PBLs are typically diagnosed in the first decade of life, with the median age being 4-5 years old (3,(6)(7)(8), although there are several cases reported in older children and adults (9)(10)(11)(12). Boys are more affected than girls.…”
Section: Pancreatoblastoma Epidemiologymentioning
confidence: 99%
“…The most effective and mainstay treatment of PBL is complete surgical resection. It is also the most important prognostic factor, with 5-year overall survival rates of >70% reported in patients without metastases who underwent R0 resection (6,18). In 81 pediatric cases of PBL, most patients underwent pancreaticoduodenectomy (PD; Whipple procedure) (44.1%), followed by spleen-preserving distal pancreatectomy (DP) (26.5%), central pancreatectomy (11.8%), tumor enucleation (11.8%), and DP with splenectomy (5.8%) (5).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In children with PBL relapse who received six cycles of PLADO chemotherapy in the first‐line treatment, ICE, VAC, or other regimens with or without anthracyclines might be therapeutic options 63 . The role of high‐dose chemotherapy with autologous peripheral blood stem cell rescue, RT and liver transplantation has not been established due to small number of patients treated with these modalities; however, these may be therapeutic strategies in selected cases (Level V; Grade C) 61,64 …”
Section: Expert/partner Recommendations For Management Of Pbl In Childrenmentioning
confidence: 99%